2016
DOI: 10.1177/1356766715626966
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human-induced environmental destruction on destination image perception and travel behaviour

Abstract: The study presented in this article provides a valuable insight into the impact of human-induced environmental destruction on the travel market’s image perceptions of a World Heritage-listed tourism icon: the Great Barrier Reef (GBR). The study employs a pre-/post-experimental design to explore how tourists are likely to respond to the media hype surrounding the construction of a port terminal, known as the Abbot Point Project, which will inevitably have some perceived environmental consequence for the ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Past studies confirmed stated that a positive destinations image contributes to the tourists' visit intention and played an important role in tourists' decision making (Chen & Tsai, 2007;Siti-Nabiha et al, 2008). Moreover, positive image perceptions towards natural tourism destinations would impact a subsequent change in conservational behavior (Salvatierra & Walters, 2015). Thus, destination image appropriately predicts future responsible environmental behavioral intentions (Lee & Gross, 2010;Luo & Deng, 2007).…”
Section: Destination Imagementioning
confidence: 99%
“…Past studies confirmed stated that a positive destinations image contributes to the tourists' visit intention and played an important role in tourists' decision making (Chen & Tsai, 2007;Siti-Nabiha et al, 2008). Moreover, positive image perceptions towards natural tourism destinations would impact a subsequent change in conservational behavior (Salvatierra & Walters, 2015). Thus, destination image appropriately predicts future responsible environmental behavioral intentions (Lee & Gross, 2010;Luo & Deng, 2007).…”
Section: Destination Imagementioning
confidence: 99%
“…Environmental damage and degradation can lead to negative travel experiences and perceptions, and thus impact tourists' revisitation. On the other hand, the authorities should effectively integrate resources to promote sustainable destinations based on trends, preferences, evaluations, and opinions from demand-side tourism (Salvatierra & Walters, 2015).…”
Section:  Resource Managementmentioning
confidence: 99%
“…This all makes Galleon a tourist in his own life, little better than the 'disaster tourists' hovering around Pitcairn Island in case it sinks in a sightseeing event organised by End of the World Touring (169). Travel literature calls this 'last chance' tourism' (Salvatierra & Walters 2017). Eloise describes him as a 'colonial reconnoitrer' (100) because he is a film auteur controlling every aspect of the production of immersive disaster films.…”
Section: Work Citedmentioning
confidence: 99%
“…Whether TEXT Special Issue 56: RE-mapping Travel Writing in the 21 st Century eds Stefan Jatschka, Stephanie Green and Nigel Krauth, October 2019 8 advertising or novelistic stories, 'recipients' project themselves into the context because, in evolutionary terms, episodic memory is a survival mechanism relating to risk management. Indeed, travel marketing literature has a deep engagement with understanding the relationships between risk perception (financial, socio-psychological, health/physical) destination image (desirable, dangerous, dirty, disappearing) and revisit intention (Salvatierra & Walters 2017;Stylos et al 2016;Chew & Jahari 2014).…”
mentioning
confidence: 99%